Studies of the Polar and Apolar Liquid Film Properties of Pure and Modified Activated Carbons by Thermal Analysis and Sorptiometric Methods - Dariusz Głażewski; Piotr Staszczuk; Roman Leboda (Adsorption Science & Technology)
Thermal analysis was used to investigate the adsorbed water layers and surface properties of various pure and modified commercial activated carbons. In addition, the thermodesorption of n-butanol, n-octane and benzene from samples saturated in a vacuum desiccator was studied under quasi-isothermal conditions. The mass loss Q-TG and differential mass loss Q-DTG curves obtained consisted of steps and inflections which were associated with the mechanism of wetting, adsorption and porosity properties of the studied surfaces. Adsorption/desorption isotherms of nitrogen on the activated carbon samples were measured using a sorptiomatic method. The specific surface areas, pore sizes, pore volumes and pore-size distribution functions have been calculated for the various samples. A correlation between the porosity parameters obtained from thermogravimetric and sorptiometric methods is presented.